End-of-Year Spending and the Long-Run Employment Effects of Training Programs for the Unemployed - Bernd Fitzenberger; Marina Furdas; Christoph Sajons (Institute of Labor Economics (IZA), 2016)
This study re-estimates the employment effects of training programs for the unemployed using exogenous variation in participation caused by budget rules in Germany in the 1980s and early 1990s, resulting in the infamous "end-of-year spending". In addition to estimating complier effects with 2SLS, we implement a flexible control-function approach to obtain the average treatment effect on the treated (ATT). Our findings are: Participants who are only selected for budgetary reasons do not benefit from training programs. However, the ATT estimates suggest modest positive effects in the long run. Longer programs are more effective than shorter and more practice-oriented programs.
Keywords: J64; J68; H43; 330; training for the unemployed; budgetary conditions; administrative data; Germany